The Distance Training Application to Improve the Literacy Ability of Mathematical Teacher on Madrasah Tsanawiyah - Makmun Hidayat; Mustadji; Bachtiar Saiful Bachri; Bakhrul Khair Amal (Britain International for Academic Research (BIAR) Publisher, 2021)
The pandemic covid-19 and the development of information technology and communication is a resistance and challenge for those who are trained to innovate the training pattern. In practice, the distance training as multimedia based learning becomes an alternative implementation pattern that is widely applied by training institutions. In the implementation of this distance training, literacy skills of the participants are required. This study aims to explain the increase in literacy skills of Madrasah Tsanawiyah mathematics teachers through the application of distance training. This study is a quantitative descriptive study on a sample of mathematics teacher training participants at the Surabaya Religious Education and Training Center in 2021. The research design used a one sample pre test-post test with a test as a data collection technique. Then the data was processed using N-Gain analysis techniques and using t-test's SPSS paired sample test method. The results showed that there was an increase in literacy ability in general by 0.842 (high Gain category) with t-test results at = 0.05, df = 34 of 16, 952 > t table (very significant category). Meanwhile, the literacy ability of mathematical content in the geometry aspect showed an increase of 0.618 (medium gain category) with t-test results at = 0.05, df = 34 of 11,153 > t table (very significant category). From the results of this study, it can be concluded that the application of distance training can improve the literacy skills of Madrasah Tsanawiyah mathematics teachers.